Radiological assessment of 40K, 238U and 232Th from soil and groundwater in Port Harcourt Metropolis, Rivers State, Nigeria - Okoro, Fidelis T.; Ekanem, Aniekan M.; Nathaniel, Ekong U.; Ndoma, Emmanuel G. (Researchers Journal of Science and Technology, 2025)
Environmental contamination by naturally occurring radionuclides is a growing concern in urban-industrial regions, where both geological processes and human activities can increase radiation exposure risks. Port Harcourt Metropolis, Nigeria, a major petroleum hub, faces potential contamination challenges in soil and groundwater, but comprehensive assessments remain limited. This study investigated the concentrations of 40K, 232Th, and 238U in soil and groundwater samples collected from residential, industrial, and natural zones. High-resolution NaI(Tl) gamma-ray spectrometry was employed to determine activity concentrations and assess radiological health risks. Soil concentrations ranged from 153.98 - 434.53 Bq/kg (40K), 16.01 -38.84 Bq/kg (232Th), and 6.01 - 15.07 Bq/kg (238U), while groundwater values ranged from 15.09 - 46.72 Bq/L (40K), 1.71 - 5.20 Bq/L (232Th), and 1.26 - 5.94 Bq/L (238U), respectively. Several groundwater samples exceeded World Health Organization (WHO) guideline limits, indicating possible chronic exposure risks. Radiological hazard indices showed spatial variability, with Rukpakwurushi New Area consistently recording higher values. The results suggest both geogenic and anthropogenic contributions, particularly from petroleum-related activities. Elevated radionuclide levels highlight potential risks through ingestion, inhalation, and external exposure, with implications for public health and aquatic food chains. The findings of this study are expected to inform environmental monitoring, guide policy interventions, and support sustainable public health management in Nigeria’s oil-producing regions.